Pregnane neurosteroids exert opposite effects on GABA and glycine-induced chloride current in isolated rat neurons - Solntseva, Elena I; Bukanova, Julia V; Skrebitsky, Vladimir G; Kudova, Eva (Hippocampus, 2022)
The ability of endogenous neurosteroids (NSs) with pregnane skeleton modified at positions C-3 and C-5 to modulate the functional activity of inhibitory glycine receptors (GlyR) and ionotropic ɣ-aminobutyric acid receptors (GABAA R) was estimated. The glycine and GABA-induced chloride current (IGly and IGABA ) were measured in isolated pyramidal neurons of the rat hippocampus and in isolated rat cerebellar Purkinje cells, respectively. Our experiments demonstrated that pregnane NSs affected IGABA and IGly in a different manner. At low concentrations (up to 5 μM), tested pregnane NSs increased or did not change the peak amplitude of the IGABA , but reduced the IGly by decreasing the peak amplitude and/or accelerating desensitization. Namely, allopregnanolone (ALLO), epipregnanolone (EPI), pregnanolone (PA), pregnanolone sulfate (PAS) and 5β-dihydroprogesterone (5β-DHP) enhanced the IGABA in Purkinje cells. Dose-response curves plotted in the concentration range from 1 nM to 100 μM were smooth for EPI and 5β-DHP, but bell-shaped for ALLO, PA and PAS. The peak amplitude of the IGly was reduced by PA, PAS, and 5α- and 5β-DHP. In contrast, ALLO, ISO and EPI did not modulate it. Dose-response curves for the inhibition of the IGly peak amplitude were smooth for all active compounds. All NSs accelerated desensitization of the IGly . The dose-response relationship for this effect was smooth for ALLO, PA, PAS and 5β-DHP, but it was U-shaped for EPI, 5α-DHP and ISO. These results, together with our previous results on NSs with androstane skeleton, offer comprehensive overview for understanding the mechanisms of effects of NSs on IGly and IGABA .
Keywords: Receptors, GABA-A; glycin; Animals; pregnany; 5alfa-dihydroprogesteron; receptory GABA-A; Neurosteroids; chloridy; Rats, Wistar; GABA; gamma-Aminobutyric Acid; Pregnanes; glycine receptor; neurony; Pregnanolone; Neurons; 5-alpha-Dihydroprogesterone; structure-activity relationship study; pregnanolon; pregnane; krysa rodu Rattus; GABAA receptor; Glycine; neurosteroidy; zvířata; Chlorides; Rats; neurosteroid; potkani Wistar